Cold-formed steel channel sections under end-two-flange loading condition: Design for edge-stiffened holes, unstiffened holes and plain webs. (February 2020) - Uzzaman, Asraf; Lim, James B.P.; Nash, David; Roy, Krishanu
Abstract: In cold-formed steel (CFS) channel sections, web holes are becoming increasingly popular. Such holes, however, result in the sections becoming more susceptible to web crippling, especially under concentrated loads applied near the web holes. Traditional web holes are normally punched or bored and are unstiffened. Recently, a new generation of CFS channel sections with edge-stiffened web holes has been developed by the CFS industry and is being widely used. However, no research is available in the literature which investigated the web crippling strength of CFS channel sections with edge-stiffened circular web holes under the end-two-flange (ETF) loading conditions. A combination of experimental tests and non-linear FEA were used to investigate the effect of such stiffened holes on web crippling behaviour under ETF loading conditions. The results of 30 web crippling tests are presented. Non-linear FE models are described, and the results are compared against the laboratory test results; a good agreement was obtained in terms of both the strength and failure modes. The results indicate that the stiffened holes can significantly improve the web crippling strength of CFS channel sections. A parametric study involving 1116 FEA was then performed, covering the effect of different hole sizes, edge-stiffener lengths and fillet radii, length of the bearing plates and position of holes in the web. Finally, design recommendations in the form of web crippling strength reduction factors are proposed, that are conservative to both the experimental and FE results. Highlights: Web crippling tests of cold-formed channel section with edge-stiffened holes under end-two-flange (ETF) loading condition were conducted. Results indicate that the stiffened holes can significantly improve web crippling strength of CFS under ETF loading conditions. Non-linear finite element (FE) models were developed and validated against the test results. A parametric study involving 1116 FE analyses was performed. Design recommendations in the form of web crippling strength reduction factors were proposed.